2014
DOI: 10.1364/oe.22.030184
|View full text |Cite
|
Sign up to set email alerts
|

Relation of the angular momentum of surface modes to the position of their power-flow center

Abstract: We show that the value of the total angular momentum (AM) carried by a surface mode can be interpreted as representing the transverse position of the center or balance point of the power flow through the mode. Especially in the lossless cases, the value of the Abraham AM per unit power (multiplied by the square of the speed of light in vacuum) is exactly the same as the transverse position of this power-flow center. However, the Minkowski counterpart becomes proportional to that position with a coefficient in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 24 publications
1
20
1
Order By: Relevance
“…Our group investigated the origin of this AM and showed that its spin component results from the rotation of the electric field comprising the surface mode [7,11]. We also proposed a geometrical interpretation that associates the total AM carried by a surface mode with the position of its power-flow center or the balance point of power flow through it [12]. (We note that a similar relation was first proposed in [13] for optical beams in free space.…”
mentioning
confidence: 64%
See 3 more Smart Citations
“…Our group investigated the origin of this AM and showed that its spin component results from the rotation of the electric field comprising the surface mode [7,11]. We also proposed a geometrical interpretation that associates the total AM carried by a surface mode with the position of its power-flow center or the balance point of power flow through it [12]. (We note that a similar relation was first proposed in [13] for optical beams in free space.…”
mentioning
confidence: 64%
“…Can we devise a surface mode whose (Abraham) SAM is parallel with its total AM (J A 0 )? (We have c 2 J A 0 ŷhz − z 0 i, where z 0 indicates the coordinate of the reference point with respect to which the total AM is defined [12].) With z 0 0, the answer is yes: if ε r μ r of the layer where the major power flows is negative, we can obtain J A 0 · S A 0 ∝ hzihκ z ∕ε r μ r i > 0 since hzihκ z i < 0 [25].…”
Section: Dng-dpg Eng-dpg Eng-mngmentioning
confidence: 99%
See 2 more Smart Citations
“…Although results of that work are erroneous in several aspects (calculation errors, mixing of the spin and orbital AM, etc), its methodology inspired us to perform microscopic calculations presented in section 4. Second, Kim and Wang aimed to calculated Abraham and 'naïve' Minkowski (without dispersion terms) versions of the transverse spin AM in SPPs [72][73][74]. However, their results are also misleading.…”
Section: About This Workmentioning
confidence: 99%